Autophagy Activation Is Involved in Acidic Fibroblast Growth Factor Ameliorating Parkinson’s Disease via Regulating Tribbles Homologue 3 - Zhong, Xingfeng; Wang, Beini; Zhang, Guanyinsheng; Yuan, Yuan; Hu, Xiaoli; Xiong, Jun; Zheng, Peipei; Liu, Yaqian; Xu, Ke; Xiao, Jian; Wu, Yanqing; Ye, Junming (Frontiers in Pharmacology, 2019)
Parkinson’s disease (PD) is a degenerative disorder of the central nervous system, resulting in loss of dopamine neurons. Excessive endoplasmic reticulum (ER) stress and autophagy dysfunction play a crucial role on Parkinson’s disease (PD) development. It has been showed that acidic fibroblast growth factor (aFGF) alleviates the development of PD by inhibiting ER stress. But the role of autophagy and its relationship with ER stress during aFGF treatment for PD has not been elucidated. We found that both aFGF and rapamycin (Rapa) improved 6-Hydroxy Dopamine (6-OHDA)-induced PD development as shown with histomorphology results in striatum and substantia nigra (SNpc). Additionally, aFGF promoted autophagy with increasing mTOR and decreasing p62 expressions, and then exerts its neuroprotective role in 6-OHDA-treated PC12 cells, which were abolished by chloroquine (CQ) treatment. Moreover, 4-phenylbutyric acid (4-PBA) administration inhibited the expressions of autophagy markers during 6-OHDA-treated PC12 cells, which was similar with aFGF treating PC12 cells under 6-OHDA condition. Furthermore, we had detected the expressions of CHOP and its downstream factor, tribbles homologue 3 (TRB3), a pro-apoptotic protein. We found that TRB3 and CHOP expressions were significantly downregulated after treating with aFGF and 4-PBA in 6-OHDA-treated PC12 cells and PD model. Taken together, this study has demonstrated that aFGF treatment ameliorates 6-OHDA-induced elevated ER stress and subsequently suppression of autophagy via inhibiting TRB3 activation, and consequently ameliorates 6-OHDA-induced neurotoxicity.